The The Arabic Aspectual Marker Qad from the Perspective of the Two-Component Theory of Aspect - Dania Adel Salamah (National Research University Higher School of Economics, 2019)
The study examined the Arabic aspectual particle qad within the framework of Smith's Two-Component Theory of Aspect, which views aspectual meaning as a combination of covert situation types and overt viewpoint markers. The analysis, which was conducted on Modern Standard Arabic, revealed that the Arabic aspectual marker qad has a tendency to be used perfectively, but it also has imperfective uses. However, as far as situation types are concerned, the analysis found some variation when it comes to the use of imperfective and perfective qad. The findings were also correlated to different constructions in which qad typically occurs.